Internal and external perspectives on pre-service teachers in Olivarez College: an ethnographic study - Cruz, Zoren S.; Sun Woo Hong; Vasquez, Dianne Erika C. (Parañaque City: Olivarez College, 2013)
This study sought to know the internal and external perspectives on pre-service teachers in Olivarez College for the researchers to be able to: 1. describe the culture of pre-service teachers in Olivarez College in terms of emic and epic perspectives. 2. determine the divergence and convergence of the perspectives of the subjects. 3. design an enhancement program for the College of Education of Olivarez College This study used Ethnographic Research that involves trying to understand how people live their lives. The researchers utilized the stratified random sampling technique in selecting the respondents. Base from the answers given by the participants, this study developed appropriate enhancement programs which will be beneficial to pre-service teachers. The researchers were able to gather data from the students of the Education department and students from other departments of Olivarez College, a principal and a cooperating teacher of a cooperating school including their gender and course. The subjects were eight (10) college students who are currently enrolled in different courses. Three (3) of them were from College of Education, one (1) from each course: Mass Communications, Psychology, Political Science, Tourism and Hotel and Restaurant Management, Computer Studies, Business and Accountancy and Health Related Sciences. The remaining two (2) were the principal and the head teacher of the cooperating school. The researchers gathered the data through the use of in-depth interviews, which were documented by the use of a video recording device. The gathered data were sorted, labeling each subject as {93}Subject (the the number){94} and was labeled as {93}internal and external{94} to easily recognize one from the other. All of the questions were answered by each subject respectively. After careful analysis of the findings, the following conclusions were drawn out: As to personal aspects from internal subject, they perceived that pre-service teachers are responsible, diligent and hard-working. The main reason why they chose education is because it is their dream to teach and that they believe that it is their calling. Subjects believed that pre-service teacher are equipped with the personality, attitude, facility of the language and are capable multi-tasking. Yet, there are still who are irresponsible and not performing the same way as the other pre-service teachers. As to personal aspects from external subject, they perceived that pre-service teachers are not yet prepared to fulfill the duties of a full-pledge teacher but there is a certainly that they can land on a job. They chose education because it is their dream to teach and that they believe that it is their calling. The reason why did not choose education is because they believe that they do now have the capabilities of being a teacher. As to environmental aspects from the internal, subjects agree that facilities would affect and reflect the performance of the pre-service teachers. In addition, subject also explained how the curriculum, objectives and professors play a big role in the development of a pre-service teacher. As to environmental aspects from external, subjects explained that facilities of the department affect the skills of the pre-service teachers in maximizing their performance. On the contrary, some subjects disagree and instead believed that facilities do not affect the performance of the pre-service teacher. Additionally, subjects all agree that professors and standardized curriculum have huge effect on the behavior and attitude on the skills of the pre-service teachers. As to environmental aspects from internal, subjects agree that there is an edge in becoming an education student among other courses. For environmental aspects from external, subjects likewise agree that there is an edge being an education student; however, comparisons among other course should not be tolerated since for him all the students are the same. As to the similarities (divergence) for personal aspects, subjects said that pre-service teachers can educate their students very well and they believe that pre-service teachers are hard working. Subjects also mentioned that pre-service teachers are versatile dealing with various situations and have the capabilities to do multi-tasking and completing tasks immediately. Nevertheless, some subjects agreed that some pre-service teachers are irresponsible and are not serious of what they are doing. While for the differences (Convergence) for personal aspects, subjects shared that some pre-service teachers are irresponsible. In the contrary, subject 11 said that they are very active in school activities. Also, Subject 5 mentioned that pre-service teachers need some encouragement whereas subject 9 said that they are confident and much focused on what they are doing. Furthermore, subject 2 stated that pre-service teachers are professional but subject 6 said that they have to be assertive. As to similarities (divergence) for the environmental aspects, subjects mentioned that the facilities of the College of Education are well-organized and facilities would serve as a basis of everything a pre-service teacher does in his everyday learning. Subjects also said that the curriculum should be standardized and all schools follow standards. In addition, subjects stated that professor have different techniques in terms of teaching which would be hard in getting the minds of their teachers. Furthermore, subjects suggested that the facilities of the College of Education should be improved. As for the differences (convergence) for the environmental aspects, Subjects believed that facilities affect the skills of pre-service teachers. On the contrary, some subjects mentioned that facilities do not affect the pre-service teachers{92} skills because Education students are passionate. Subjects also mentioned that facilities can sometimes affect, but most of the time it affect the performance of the pre-service teachers. In addition, subjects responded that the College of Education has the quality and standard comparable to other good quality colleges in the area but accordance to the new technologies. As to the similarities (divergence) for behavioral aspects, subjects stated that pre-service teachers have an edge because Education is the noblest profession and they are equipped of extra-ordinary knowledge and it is the mother of all courses. In addition, subjects explained that being a pre-service teacher is not only about teaching, it is also exploring things in being trained to educate people. With regard to the differences (convergence)for behavioral aspects, subject 5 mentioned that there is an edge being a pre-service teacher compared to other courses because they do not just teach them concepts but prepare them as well whereas subject 8 stated that they don{92}t have an edge because they just all look the same, and to be fair as well. Considering the findings and conclusion of this study, the following are hereby recommended by the researchers: As to personal aspects, there should be an early exposure for younger levels of education students by conducting an activity that caters to non-education students like, English proficiency lecture to showcase their readiness in becoming a future mentor. There should also be a group of professors or students who are already enrolled in the college of education that will orient incoming college students about the Education course, so as to have a bird{92}s eye view of what it is like to be in the education department. Speaker should enlighten them that skills and knowledge of being a teacher can be learned during their stay in college. There should be more professional educational subjects which could build the personalities pre-service teachers into more dynamic molds. Implementing other professional educational subjects would strengthen the individualities and enhance the skills of the pre-service teachers. There should be diagnostic tests from which the college of education could gather information about the strengths and weaknesses of each student. Moreover, as the institution collects information, they simultaneously determine what teaching strategies and methodologies should be implemented for the pre-service teachers.
As to environmental aspect, there should be more improved and modern technologies and classrooms in the College of Education at Olivarez College. A conductive learning environment would entail higher-order thinking capabilities of students to prepared themselves into a globally competitive one. As to environmental aspect, there should be more improved and modern technologies and classrooms in the College of Education at Olivarez College. A conductive learning environment would entail higher-order thinking capabilities of students to prepared themselves into a globally competitive one. As to behavioral aspect, there should be marketing strategies concerning the frame of pre-service teachers among other courses like elevating the career opportunities for teacher hopefuls as well as the achievements of pre-service teachers in the field of Education. As per general recommendation, there should be a follow-up research about the perspectives on pre-service teachers to ensure that each designed program is effective for the College of Education.
Undergraduate Thesis
Keywords: Pre-service teachers